(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Dyslipidemia is defined as abnormal amount of lipids in the blood. It is a metabolic disorder, manifested as increased plasma levels of total cholesterol, triglyceride or a decrease in high density lipoprotein. Dyslipidemia is the main disposing factor for the atherosclerosis, and the atherosclerosis is the main pathogenesis factor for cardiovascular disease. In Ayurvedic view, dyslipidemia can be considered similar to aggravated Dusta Meda Dhatu in the body which is caused due to hypofunction of Medo-Dhatwagni leading to Medovaha Srotodusti Vikara. Nidanparivarjana is the main treatment principle of Ayurveda. For dyslipidemia, diet which is Laghu, Ruksha, Kaphamedohara and Srotoshodhana property should be followed. While, Guru, Snigdha, Kaphamedokara and Abhishyandhi food should be avoided. According to Bhaisjya Ratnawali, Pathya for Hridroga are Dadima, Shunthi, Yavani, Patol etc while Apathya are Ksheer Vikruti, Dadhi, Guru Bhojan etc. Using healthy diet rich in complex carbohydrates, vegetables, and fruits seasoned with adequate quantity of spices with minimum amount of oils and fats are ideal for management and prevention of dyslipidemia. So this research article, will explain the properties of Pathya and Apathya their mode of action in prevention and management of dyslipidemia with the help of previous research work done on related Pathya Apathya food article.